OPTIMIZATION OF NITROGEN-ALLOYED MoSx COATING FOR LOW FRICTION APPLICATIONS - Kannur, Kaushik Hebbar (2021)
Doctoral Thesis in Mechanical Engineering, Surface Engineering Branch, submitted to the Department of Mechanical Engineering, Faculty of Science and Technology of the University of Coimbra.